The "Dark Side" of Creativity: Exploring the Relationship Between Creativity and Unethical Behavior - Miftahuddin Miftahuddin; Faisal Razak; Syafiq Amir (Journal of Loomingulisus ja Innovatsioon, 2025)
The growing body of research on creativity has traditionally highlighted its positive contributions to innovation and problem-solving, yet recent studies suggest that creativity may also facilitate unethical behavior. This study investigates the “dark side” of creativity by examining how creative potential and creative self-efficacy relate to morally questionable decision-making in organizational contexts. The research aims to clarify whether creativity inherently increases individuals’ capacity to rationalize misconduct or whether situational factors moderate this relationship. A mixed-method design was employed, combining a quantitative survey of 312 employees from diverse professional sectors with qualitative vignette-based interviews to probe moral reasoning processes. The findings indicate that higher creativity scores correlate with greater justification of rule-bending behaviors, particularly when individuals perceive ethical norms as ambiguous or organizational climates as permissive. However, creativity did not uniformly predict unethical actions; rather, the effect was contingent upon motivational orientations and moral disengagement tendencies. The study concludes that creativity is a dual-edged construct capable of generating both adaptive and maladaptive outcomes highlighting the need for ethical scaffolding in creative work environments. These insights contribute to a more nuanced understanding of creativity beyond its celebrated positive dimensions.